The Granger Causality Between Corruption and Economic Growth in ASEAN Countries - Li, Li (Archives of Business Research, 2022)
This paper studies the Granger causality between corruption and economic growth in ASEAN countries over the period of 1995-2019. Ten ASEAN countries are Brunei Darussalam, Cambodia, Indonesia, Lao People's Democratic Republic, Malaysia, Myanmar, Philippines, Thailand, Vietnam, and Singapore. The corruption is measured by the Corruption Perception Index published annually by Transparency International. The economic growth is measured by a country’s annual gross domestic product growth rate. There is a significant bidirectional Granger causality found between lower level of corruption and higher economic growth in Indonesia. It is shown that higher economic growth Granger causes lower level of corruption in Brunei Darussalam, and lower level of corruption Granger causes higher economic growth in Cambodia. No Granger causality between corruption and economic growth is found in the remaining seven ASEAN countries.